We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
632
2
avatar+12 

Prove that Log 5/36 - log 5/9 = -log 4

 Aug 24, 2015

Best Answer 

 #2
avatar+99580 
+5

Log 5/36 - Log 5/9 = -log 4 ....  and we can write....

 

log [(5/36) / (5/9)] =

 

log [ (5/36) ( 9/5) ] =

 

log (9 / 36)  =

 

log ( 1 /4)  =

 

log 4-1  =

 

(-1)log 4)  =

 

-log 4

 

 

 Aug 24, 2015
 #1
avatar
0

Prove that Log 5/36 - log 5/9 = -log 4......... IS FALSE!!!!!!!!!!!!!

Log 5/36-Log 5/9=Log 1/4

 Aug 24, 2015
 #2
avatar+99580 
+5
Best Answer

Log 5/36 - Log 5/9 = -log 4 ....  and we can write....

 

log [(5/36) / (5/9)] =

 

log [ (5/36) ( 9/5) ] =

 

log (9 / 36)  =

 

log ( 1 /4)  =

 

log 4-1  =

 

(-1)log 4)  =

 

-log 4

 

 

CPhill Aug 24, 2015

7 Online Users